1950
DOI: 10.1111/j.1151-2916.1950.tb12765.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Sapphirine and Its Stability Relations in the System MgO‐Al2O3‐SiO2

Abstract: A compound corresponding in optical properties and in X-ray powder pattern with the natural mineral sapphirine has been synthesized by repeated sintering of the constituent oxides at atmospheric pressure.The most probable formula for this synthetic compound is 4Mg0.-5Al2O3. 2Si02. An unidentified crystalline phase previously noted in certain magnesia-aluminasilica porcelains has been shown to be identical with this synthetic sapphirine. There is reason to believe that sapphirine possesses a small field of prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1957
1957
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…The formula of sapphirine was assumed to be Mg 4 Al 10 Si 2 O 23 following Osborn and Muan [86] and Foster. [87] Sub-solidus phase equilibria were investigated by several authors [85,[87][88][89] using a sintering technique and x-ray phase determination. Smart and Glasser [89] and Foster [87] reported that the (sapphirine + corundum + mullite) phase assem- blage transformed to (spinel + mullite + corundum) above about 1460°C.…”
Section: Summary Of Available Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The formula of sapphirine was assumed to be Mg 4 Al 10 Si 2 O 23 following Osborn and Muan [86] and Foster. [87] Sub-solidus phase equilibria were investigated by several authors [85,[87][88][89] using a sintering technique and x-ray phase determination. Smart and Glasser [89] and Foster [87] reported that the (sapphirine + corundum + mullite) phase assem- blage transformed to (spinel + mullite + corundum) above about 1460°C.…”
Section: Summary Of Available Experimental Datamentioning
confidence: 99%
“…[87] Sub-solidus phase equilibria were investigated by several authors [85,[87][88][89] using a sintering technique and x-ray phase determination. Smart and Glasser [89] and Foster [87] reported that the (sapphirine + corundum + mullite) phase assem- blage transformed to (spinel + mullite + corundum) above about 1460°C. Smart and Glasser [89] reported that the (sapphirine + cordierite + corundum) phase assemblage transformed to (sapphirine + cordierite + mullite) above about 1386°C.…”
Section: Summary Of Available Experimental Datamentioning
confidence: 99%
“…The total admixture content may be from 5 to 20 vol.%. All well-known conventional methods that activate the synthesis process⎯common fine grinding, increase in annealing temperature and duration, introduction of fluxes and mineralizers as alkaline oxides, B 2 O 3 , MnO 2 , and tungsten and molybdenum compounds⎯decrease the cordierite formation temperature to 1220-1250°C [3] but do not increase its amount. According to [4], the liquid phase formed after introduction of alkali metal oxides into the charge greatly activates crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…For ternary equilibrium diagram see figure 9; lowest ternary eutectic with MgO• Si02, Tridymite and Cordierite, 1345°C. (Rankin and Merwin, 191a;Bowen and Greig, 1924;Greig, 1927a;Schairer, 1942;Foster, 1950Foster, , 1951aKeith and Schairer, 1952. ) 2Mn0• 2A1203· 5Si02, (2:2:5), Manganese Cordierite, incongruent melting to mullite and liquid about usaoc.…”
Section: Mg0-si0 2 Melting and Transformation Temperatures Dl9mentioning
confidence: 99%
“…reprinted by permission of the Journal of Geology; copyright, 1952, by the University of Chicago. Composite diagram based on Rankin and Merwin (1918), Bowen and Greig (1924), Greig (1927a), Schairer (1942), andFoster (1950). Ricker and Osborn (1954); reprinted by permission of the American Ceramic Society.…”
Section: System Miscellaneousmentioning
confidence: 99%